2022
DOI: 10.2147/jir.s374304
|View full text |Cite
|
Sign up to set email alerts
|

Differences in B-Cell Immunophenotypes and Neutralizing Antibodies Against SARS-CoV-2 After Administration of BNT162b2 (Pfizer-BioNTech) Vaccine in Individuals with and without Prior COVID-19 - A Prospective Cohort Study

Abstract: Purpose Understanding the humoral immune response dynamics carried out by B cells in COVID-19 vaccination is little explored; therefore, we analyze the changes induced in the different cellular subpopulations of B cells after vaccination with BNT162b2 (Pfizer-BioNTech). Methods This prospective cohort study evaluated thirty-nine immunized health workers (22 with prior COVID-19 and 17 without prior COVID-19) and ten subjects not vaccinated against SARS-CoV-2 (control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Transitional B-cells are immature forms of B-lymphocytes, serving as mature B-cell precursors. Their maturation process depends on their Ag exposure and results in the translocation of the produced mature cells into germ centers, where they can differentiate into memory cells and, finally, plasma cells [18]. Consequently, it was not to our surprise that patients who effectively responded to the third dose had demonstrated more elevated concentrations of that particular subpopulation at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Transitional B-cells are immature forms of B-lymphocytes, serving as mature B-cell precursors. Their maturation process depends on their Ag exposure and results in the translocation of the produced mature cells into germ centers, where they can differentiate into memory cells and, finally, plasma cells [18]. Consequently, it was not to our surprise that patients who effectively responded to the third dose had demonstrated more elevated concentrations of that particular subpopulation at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the BNT162b2 vaccine induces changes in B-cell subpopulations, especially generating plasma cells and producing neutralizing antibodies against SARS-CoV-2. Moreover, previous infection with SARS-CoV-2 did not significantly alter the dynamics of these subpopulations but induced more rapid and optimal antibody production [21]. In this study, we found a reduction of naive B cells and an increase in IgM-memory, switched-memory, and CD21 low B cells in SSc patients after vaccination.…”
Section: Discussionmentioning
confidence: 41%
“…B-cell concentration has been strongly correlated with SARS-CoV-2 antibody production in immunocompromised patients ( 24 ). However, this association has not been observed in immunocompetent patients ( 25 , 26 ). Our results, showing decreased B-cell concentrations in vaccinated patients, may indicate a suboptimal B-cell function in these patients, which would potentially contribute to hospital admission despite vaccination.…”
Section: Discussionmentioning
confidence: 86%
“…A reduced humoral response following vaccination could contribute to impaired COVID-19 immunity and hence admission to hospital despite COVID-19 vaccination. B-cell concentration has been strongly correlated with SARS-CoV-2 antibody production in immunocompromised patients (24). However, this association has not been observed in immunocompetent patients (25, 26).…”
Section: Discussionmentioning
confidence: 99%